Institute of Development Studies annual report 1985 : handbook 1986 - Institute of Development Studies (Brighton, England) (Brighton, England : IDS Sussex, 1985)
The book contains the annual report of Institute of Development Studies research and programmes especially in the developing countries.
usc 10/04/2019
Ref.
Keywords: Economic development; Economic history; Developing countries